1994 Agreement on the implementation of Part XI of the UN Convention on the Law of the Sea : breakthrough to universality? - BROWN, E.D. (1995)
Considers the implications for the universality of the Convention of the adoption in July 1994 of an Agreement to Implement Part XI of the Convention. Adopted with the support of the industrialised states, the new Agreement which, in reality substantially amends the seabed mining regime in Part XI of the UN Convention - almost certainly ensures that the three non-signatory states, Germany, the United Kingdom and the United States, will accede to the Convention, and that the Convention will achieve near-universality in the not too distant future. One of the implications of the entry into force of the Convention is that the international community now has in place a complex system for the compulsory settlement of disputes.